The genomic landscape of cutaneous SCC reveals drivers and a novel azathioprine associated mutational signature - Gareth J. Inman (Nature Portfolio, 2018)
It is known cutaneous squamous cell carcinoma (cSCC) involves a high tumour mutation burden. Here the authors identify common cSCC mutated genes, copy number changes, altered pathways and report the presence of a novel mutation signature associated with chronic exposure to the immunosuppressive drug azathioprine.